2004
DOI: 10.1016/j.fluid.2004.05.011
|View full text |Cite
|
Sign up to set email alerts
|

A molecular simulation study of shear and bulk viscosity and thermal conductivity of simple real fluids

Abstract: Shear and bulk viscosity and thermal conductivity for argon, krypton, xenon, and methane and the binary mixtures argon+krypton and argon+methane were determined by equilibrium molecular dynamics with the Green-Kubo method. The fluids were modeled by spherical Lennard-Jones pair-potentials with parameters adjusted to experimental vapor liquid-equilibria data alone. Good agreement between the predictions from simulation and experimental data is found for shear viscosity and thermal conductivity of the pure fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 53 publications
3
61
0
1
Order By: Relevance
“…Fernandez et al 27 demonstrated that, contrary to bulk viscosity, the values of shear viscosity of argon obtained from molecular dynamics simulation of a Lennard-Jones system agree with experimental data. Lee and Cummings 44 and Marcelli et al 46 found that the influence of triple-dipole interaction on shear viscosity of argon is small.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Fernandez et al 27 demonstrated that, contrary to bulk viscosity, the values of shear viscosity of argon obtained from molecular dynamics simulation of a Lennard-Jones system agree with experimental data. Lee and Cummings 44 and Marcelli et al 46 found that the influence of triple-dipole interaction on shear viscosity of argon is small.…”
Section: Resultsmentioning
confidence: 85%
“…Nevertheless, experimental data on self-diffusion, shear viscosity, and thermal conductivity coefficients of argon have been shown to be accurately described by Lennard-Jones model with the parameters obtained by fitting thermodynamic data. 26,27 Bulk viscosity is a noticeable exception. Bulk viscosity of argon has been measured experimentally, [28][29][30][31][32][33][34][35] and its behavior can be qualitatively described by the results of a molecular dynamics simulation of a Lennard-Jones system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because in dense gases and normal liquids S͑t͒ decays on the microscopic time scale of molecular collisions, it can be readily evaluated by MD simulation. 19 This situation will be considered further in Sec. V. In the supercooled regime the relevant dynamics is system activation over deep energy minima.…”
Section: Computing Viscosity Via Transition State Pathway Samplinmentioning
confidence: 96%
“…Several methodologies based on equilibrium and non-equilibrium MD were developed to predict thermodynamic and transport properties, including thermal diffusion coefficients (Artola and Rousseau, 2013). Transport properties such as thermal conductivity, viscosity and diffusion coefficient can be computed by equilibrium MD using the wellknown Green-Kubo relations Fernández et al, 2004;Liang and Tsai, 2010). For coupled transport properties, the most successful methods are the Synthetic Non-Equilibrium Molecular Dynamics (S-NEMD) and the Boundary-driven Non-Equilibrium Molecular Dynamics (BD-NEMD) methods.…”
Section: Brazilian Journal Of Chemical Engineeringmentioning
confidence: 99%